Full scale laboratory testing of ballast and concrete slab tracks under phased cyclic loading. (1st December 2018) - Marolt Čebašek, T.; Esen, A.F.; Woodward, P.K.; Laghrouche, O.; Connolly, D.P.
Abstract: Full-scale laboratory-based testing is used to compare the long-term settlement performance of a precast concrete slab track section to a ballasted track (with concrete sleepers) resting on a compacted substructure. The railway track substructure is constructed from a 1.2 m deep combined subgrade and frost protection layer, according to modern high-speed rail standards such as those specified in Germany. Phased cyclic loading is then used to simulate the primary loading mechanism of a train after 3.4 million load cycles representing many years' worth of train passages. Displacement transducers, earth pressure cells and accelerometers are employed to determine the permanent settlement, the cyclic displacement, transient stresses and vibrations of the track. The equipment, loading combinations, material properties and experimental displacement results are presented and compared. The results indicate that the ballasted track experienced 20 times more settlement when compared to the concrete slab track under the same loading conditions, even though the ballasted track was tested at a slightly higher compacted state due to the concrete slab track test being conducted first.